2021
DOI: 10.3390/toxins13050320
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification and Excretion of Trichothecenes in Transgenic Arabidopsis thaliana Expressing Fusarium graminearum Trichothecene 3-O-acetyltransferase

Abstract: Fusarium graminearum, the causal agent of Fusarium head blight (FHB), produces trichothecenes including deoxynivalenol (DON), nivalenol (NIV), and 3,7,15-trihydroxy-12,13-epoxytrichothec-9-ene (NX-3). These toxins contaminate grains and cause profound health problems in humans and animals. To explore exploiting a fungal self-protection mechanism in plants, we examined the ability of F. graminearum trichothecene 3-O-acetyltransferase (FgTri101) to detoxify several key trichothecenes produced by F. graminearum: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…They cloned FgTri101 from Fusarium graminearum and expressed it in Arabidopsis plants. The experimental results confirmed that FgTri101 transgenic plants can acetylate DON to 3-ADON, as well as 15-ADON to 3,15-diDON ( Hao et al, 2021 ). Furthermore, Wang et al found that 3-ADON and 15-ADON can be deacetylated to produce DON, which is then degraded into 3-keto-DON ( Wang N. et al, 2019 ).…”
Section: Biological Methodssupporting
confidence: 63%
“…They cloned FgTri101 from Fusarium graminearum and expressed it in Arabidopsis plants. The experimental results confirmed that FgTri101 transgenic plants can acetylate DON to 3-ADON, as well as 15-ADON to 3,15-diDON ( Hao et al, 2021 ). Furthermore, Wang et al found that 3-ADON and 15-ADON can be deacetylated to produce DON, which is then degraded into 3-keto-DON ( Wang N. et al, 2019 ).…”
Section: Biological Methodssupporting
confidence: 63%
“…Previous studies on the biochemical process of DON detoxification and sequestration have identified five major gene families for mycotoxin detoxification in cereals: UGTs, GSTs, CYP450s, ABC transporters, and MATE (Figure 3; Gardiner, Boddu et al., 2010; Gunupuru et al., 2017; Hao et al., 2021; Lemmens et al., 2005; Li et al., 2010; Pan et al., 2018). While several genes associated with DON detoxification were unique to either the Wilkin DEG group or the AAC Tenacious DEG group, the vast majority of the DON detoxification and sequestering genes identified were common to both the resistant and susceptible responses (Table 4; Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Tri5 is the first gene in DON biosynthesis. Tri6 and Tri10 are unigenes that regulate the synthesis of DON [42]. Fusarium's self-protection mechanism pumps the toxin out of the cell through Tri12 and reduces the toxicity of intermediates in the biosynthesis of trichothecenes through Tri101 [42].…”
Section: The Effect Of Thymol On Don Production By F Graminearummentioning
confidence: 99%
“…Tri6 and Tri10 are unigenes that regulate the synthesis of DON [42]. Fusarium's self-protection mechanism pumps the toxin out of the cell through Tri12 and reduces the toxicity of intermediates in the biosynthesis of trichothecenes through Tri101 [42]. Thymol can reduce the expression of Tri5 [43] and inhibit the function of the toxin efflux pump, thereby enhancing the sensitivity of the fungus to tetracycline and benzalkonium chloride [44].…”
Section: The Effect Of Thymol On Don Production By F Graminearummentioning
confidence: 99%